Analysis of the links between Carbon Emissions and Economic Activity"Towards Inclusive Green Growth in Syria" (Damascus University Journal for the economic and Political sciences, 2024)
The research aims to study the impact of Carbon Dioxide Emissions on Economic Growth in Syria during the period 1980-2022, using the Autoregressive Distributed Lag method (ARDL). The Unit Root test was conducted to ensure the stationary of the time series, then the Bounds test was performed to verify the existence of a long-term relationship. The short-term relationship was estimated using the Unrestricted Error Correction Model (UECM). The Dynamic Cumulative Multiplier (CDM) was also used to ensure the reliability of the analysis. The results showed a positive and significant relationship between Carbon Dioxide Emissions and Economic Growth in both the long and short term, indicating the existence of an Environmental Kuznets Curve (EKC). The results also showed that Government Expenditure, Financial Remittances, Human Capital, and Financial Development have a positive impact on Economic Growth. This study provides insights into the challenges facing Syria in achieving its Climate and Development Goals, and suggests ways to enhance Inclusive Green Growth through Economic and Financial Reforms and investment in Clean Technologies.
Keywords: Inclusive Green Growth; Carbon Dioxide Emissions; Economic Growth; Environmental Kuznets Curve; Sustainable Development; Syria